Effectiveness of 10 and 13-valent pneumococcal conjugate vaccines against invasive pneumococcal disease in European children: SpIDnet observational multicentre study. Issue 29 (23rd June 2022) - Savulescu, Camelia; Krizova, Pavla; Valentiner-Branth, Palle; Ladhani, Shamez; Rinta-Kokko, Hanna; Levy, Corinne; Mereckiene, Jolita; Knol, Mirjam; Winje, Brita A.; Ciruela, Pilar; de Miguel, Sara; Guevara, Marcela; et al.
Highlights: PCV10 and PCV13 protect similarly against invasive disease due to vaccine serotypes. PCV13 provides direct protection against serotype 3 and vaccine-related serotype 6C. PCV10 does not provide significant protection against vaccine-related serotypes 19A and 6C. PCV13 effectiveness declined with time after booster, in particular for serotypes 3 and 19A. Multinational networks are crucial for the evaluation of PCV15/ PCV20 that may be introduced. Abstract: Background: Pneumococcal conjugate vaccines covering 10 (PCV10) and 13 (PCV13) serotypes have been introduced in the infant immunization schedule of most European countries in 2010–11. To provide additional real-life data, we measured the effectiveness of PCV10 and PCV13 against invasive pneumococcal disease (IPD) in children of 12 European sites (SpIDnet). Methods: We compared the vaccination status of PCV10 and PCV13 serotype IPD (cases) to that of nonPCV13 serotype IPD (controls) reported in 2012–2018. We calculated pooled effectiveness as (1-vaccination odds ratio)*100, and measured effectiveness over time since booster dose. Results: The PCV13 and PCV10 studies included 2522 IPD cases from ten sites and 486 cases from four sites, respectively. The effectiveness of ≥ 1 PCV13 dose was 84.2% (95 %CI: 79.0–88.1) against PCV13 serotypes (n = 2353) and decreased from 93.1% (87.8–96.1) < 12 months to 85.1% (72.0–92.1) ≥ 24 months after booster dose. PCV13 effectiveness of ≥ 1 dose was 84.7% (55.7–94.7) against fatal PCV13 IPD, 64.5% (43.7–77.6), 83.2% (73.7–89.3) and 85.1% (67.6–93.1) against top serotypes 3, 19A and 1, respectively, and 85.4% (62.3–94.4) against 6C. Serotype 3 and 19A effectiveness declined more rapidly. PCV10 effectiveness of ≥ 1 dose was 84.8% (69.4–92.5) against PCV10 serotypes (n = 370), 27.2% (-187.6 to 81.6) and 85.3% (35.2–96.7) against top serotypes 1 and 7F, 32.5% (-28.3 to 64.5) and −14.4% (-526.5 to 79.1) against vaccine-related serotypes 19A and 6C, respectively. Conclusions: PCV10 and PCV13 provide similar protection against IPD due to the respective vaccine serotype groups but serotype-specific effectiveness varies by serotype and vaccine. PCV13 provided individual protection against serotype 3 and vaccine-related serotype 6C IPD. PCV10 effectiveness was not significant against vaccine-related serotypes 19A and 6C. PCV13 effectiveness declined with time after booster vaccination. This multinational study enabled measuring serotype-specific vaccine effectiveness with a precision rarely possible at the national level. Such large networks are crucial for the post-licensure evaluation of vaccines.